INSPECT: A graphical user interface software package for IDARC-2D - AlHamaydeh, Mohammad (2016)
Modern day Performance-Based Earthquake Engineering (PBEE) pivots about nonlinear analysis and its feasibility. IDARC-2D is a widely used and accepted software for nonlinear analysis; it possesses many attractive features and capabilities. However, it is operated from the command prompt in the DOS/Unix systems and requires elaborate text-based input files creation by the user. To complement and facilitate the use of IDARC-2D, a pre-processing GUI software package (INSPECT) is introduced herein. INSPECT is created in the C# environment and utilizes the .NET libraries and SQLite database. Extensive testing and verification demonstrated successful and high-fidelity re-creation of several existing IDARC-2D input files. Its design and built-in features aim at expediting, simplifying and assisting in the modeling process. Moreover, this practical aid enhances the reliability of the results and improves accuracy by reducing and/or eliminating many potential and common input mistakes. Such benefits would be appreciated by novice and veteran IDARC-2D users alike.